REPRESENTASI WOMEN EMPOWERMENT PADA TOKOH DASIYAH DALAM SERIAL NETFLIX “GADIS KRETEK” - Octavia, Jelena; Noor Rakhmad, wiwid; Bayu Widagdo, Muhammad (Interaksi Online, 2024)
Women's empowerment is an effort made by women to gain control over their lives. In films or drama series, women are often portrayed as passive beings, and it is not uncommon for films or drama series to depict how women are subordinated due to the operation of patriarchal culture in society. Women's access and movement are restricted, domestication is considered something natural, and women's opinions or voices are either not taken into account or ignored. The Gadis Kretek series offers an alternative idea, presenting empowered women. This study aims to describe how women's empowerment is portrayed in the Gadis Kretek series. It is a qualitative study using a critical paradigm. The research employs A.J. Greimas' narrative analysis method, which involves three models of analysis: actantial analysis, spatio-temporal isotopy, and the semiotic square. The theories used include muted-group theory, representation theory, and are supported by the liberal feminism perspective. The results of this study show that women have their own ways of gaining control over their lives, one of which is by having inner courage. The courage possessed by the main female character in the Gadis Kretek series, Dasiyah, drives her to keep pursuing her dreams. Dasiyah is portrayed as a woman who is different from other women of that time. She has modern ideas that clash with the norms of that era. Dasiyah has the courage to challenge societal and organizational cultures that disadvantage her as a woman. However, the series also illustrates how patriarchal culture still permeates various aspects of society, especially within the family and workplace. Therefore, Dasiyah’s process of achieving success and fulfilling her desires or dreams still involves the role of men. This demonstrates that men's voices carry more weight in decision-making compared to women's.